Pros and Cons of Semester System Program under the faculty of education TU - Rayamajhi, Om Bahhadur (Educational Journal, 2023)
This article deals with the pros and cons of the Semester System Program under the Faculty of Education, Tribhuvan University, Nepal. This study has sought to understand and analyze students’ perception towards semester system taking a case of the Faculty of Education related campuses with regard to (a) academic resources, (b) physical resources, (c) governance and image, and (d) overall perception of students and teachers. It followed descriptive research design using questionnaire survey instrument, sematic-chart and check lists. Only one constituent campus was selected in Kathmandu through purposive under non-probability sampling procedure for this study. From this study, it was found that the semester system is better than annual system in terms use of better teaching equipment, efficiency of teachers and students’ performance and results. But in semester system, students’ participation in teaching learning activities has increased, they have improved skills in using electronic tools and presenting skills. Even teachers’ knowledge in using software improved. Although most of the classes under semester system were better equipped, they still lack required equipment and even skilled teachers. Similarly, the campuses running semester system were found facing shortage of budget for the sustainability of the programme. As it was taking months to publish results, it needs correction so that the students get their exam results in time. Moreover, the academic calendar was not followed duly. Likewise, those students who did not meet 80 per cent attendance were also allowed to fill up exam forms and this tendency culminated in poor results and lack of disciplined not only among students but the whole system. Unless these shortcomings are corrected, the semester cannot be effective as was expected during its introduction in 2016.